Coping style, posttraumatic stress symptomatology, and fear of crime in victims of crime. - Scott, Nicolene (My University, 2013)
This study aimed to examine the relationships between crime exposure and posttraumatic stress symptomatology, and crime exposure and fear of crime. More specifically it set out to establish a possible causal link between crime exposure and posttraumatic stress symptomatology and fear of crime. In addition, it then aimed to identify and explore the possible moderating effect of coping style, (problem-focused, emotion-focused and dysfunctional coping) on the afore-mentioned relationships. The study was conducted on a Johannesburg based, tertiary student population (n = 123) and employed self-report questionnaires to solicit responses which were then subject to statistical analyses. Findings for the relationship between crime exposure and posttraumatic stress symptomatology indicated that increased exposure to crime was predictive of higher posttraumatic stress symptomatology. However a comparison of the relationship between non-crime related traumas and posttraumatic stress symptomatology suggested that crime exposure was not the only predictor of posttraumatic stress symptomatology. Similarly, findings for the relationship between crime exposure and fear of crime indicated that increased exposure to crime was predictive of increased fear of crime levels. Again, however, a comparison of the relationship between non-crime related traumas and fear of crime suggested that crime exposure was not the only predictor of fear of crime. In reference to the possible moderating effects of coping styles on the relationships between crime exposure and posttraumatic stress symptomatology, and crime exposure and fear of crime, no significant moderating effects were found for problem-focused, emotion-focused or dysfunctional coping. Dysfunctional coping was significantly associated with higher levels of traumatic stress symptomatology and fear of crime, but independent of exposure patterns. Visible patterns of relationship with regard to both problem focused and emotion focused coping appeared to be more complex than would be expected based on existing findings in the literature.
Keywords: Post-traumatic stress disorder--South Africa.; Victims of crimes--South Africa.; Fear of crime--South Africa.; Adjustment (Psychology)--South Africa.